Gut microbiota, metabolome and immune signatures in patients with uncomplicated diverticular disease. Issue 7 (12th September 2016) - Barbara, Giovanni; Scaioli, Eleonora; Barbaro, Maria Raffaella; Biagi, Elena; Laghi, Luca; Cremon, Cesare; Marasco, Giovanni; Colecchia, Antonio; Picone, Gianfranco; Salfi, Nunzio; Capozzi, Francesco; Brigidi, Patrizia; et al.
Abstract : Objective: The engagement of the gut microbiota in the development of symptoms and complications of diverticular disease has been frequently hypothesised. Our aim was to explore colonic immunocytes, gut microbiota and the metabolome in patients with diverticular disease in a descriptive, cross-sectional, pilot study. Design: Following colonoscopy with biopsy and questionnaire phenotyping, patients were classified into diverticulosis or symptomatic uncomplicated diverticular disease; asymptomatic subjects served as controls. Mucosal immunocytes, in the diverticular region and in unaffected sites, were quantified with immunohistochemistry. Mucosa and faecal microbiota were analysed by the phylogenetic platform high taxonomic fingerprint (HTF)-Microbi.Array, while the metabolome was assessed by 1 H nuclear magnetic resonance. Results: Compared with controls, patients with diverticula, regardless of symptoms, had a >70% increase in colonic macrophages. Their faecal microbiota showed depletion of Clostridium cluster IV. Clostridium cluster IX, Fusobacterium and Lactobacillaceae were reduced in symptomatic versus asymptomatic patients. A negative correlation was found between macrophages and mucosal Clostridium cluster IV and Akkermansia . Urinary and faecal metabolome changes in diverticular disease involved the hippurate and kynurenine pathways. Six urinary molecules allowed to discriminate diverticular disease and control groups with >95% accuracy. Conclusions: Patients with colonic diverticular disease show depletion of microbiota members with anti-inflammatory activity associated with mucosal macrophage infiltration. Metabolome profiles were linked to inflammatory pathways and gut neuromotor dysfunction and showed the ability to discriminate diverticular subgroups and controls. These data pave the way for further large-scale studies specifically aimed at identifying microbiota signatures with a potential diagnostic value in patients with diverticular disease.